Allometry and stilt root structure of the Neotropical palm Euterpe precatoria (Arecaceae) across sites and successional stages - Ávalos Rodríguez, Gerardo (2010)
The lack of secondary meristems shapes allometric relationships of the palms, infl uencing species segregation according to their capacity to adjust form and function to spatial and temporal changes in environmental conditions. We examined the stem height vs. diameter allometry of Euterpe precatoria across environmental gradients and measured how terrain inclination and palm size affected stilt root structure at two sites in Costa Rica. We dissected the root cone into eight variables and used principal component analysis to summarize their correlation structure. The fi t of the stem diameter – height relationship to the stress, elastic, and geometric similar- ity models was examined using data from 438 palms. Terrain inclination did not affect stilt roots, whose structure was determined by palm size. Palms under 1 m showed geometric similarity, whereas palms above 1 m had slope values that were one and a half times higher, independent of successional stage, and did not adjust to any mechanical model. Taller palms departed from these models when they were large because they had stilt root support. We conclude that height in E. precatoria is constrained by structural support at the base and that diameter at the base of the stem and stilt roots balances height increments over all the size ranges examined. Key